Development of a Health Education Application Smartphone-based FoCED to Increase Knowledge About Foot Care In Patients With Diabetes Mellitus - Djoko Priyono; Suriadi Suriadi; Yoga Pramana; Junaidi Junaidi (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
One such complication is a diabetic foot ulcer that can lead to amputation. Various strategies are taken to reduce the occurrence of injuries in diabetic mellitus patients. One of them is through foot care education packaged by using interesting media. Through the development of smartphone-based applications, it aims to help patients and families perform the right foot care anytime and anywhere. The purpose of this activity is to develop educational media while increasing the knowledge of patients and families about performing foot care. The method used is to develop educational media in the form of applications on smartphones and measure knowledge score before and after education. In addition, during the education of patients and families, they will be followed up 3 times in 1 week. The targets of this program are diabetic patients and families at PKU Muhammadiyah Pontianak Clinic. The results of this activity show that smartphone-based